Switchmode power supply training modules - Vitug, Joseph Michael A.
The project involves the design and creation of switchmode power supply training modules which will aid in the instruction of power electronics. Two (2) DC-DC converter configurations will be the basis for the modules to be produced. The buck and flyback topologies will be utilized for the DC-DC converter training modules. The project would also involve the creation of experiments which will support the observation of switchmode power supply circuit operation.